Resource constraints and economic policy - Yeva Nersisyan (Levy Economics Institute of Bard College, 2024)
This paper explains the MMT approach for evaluating the affordability of spending programs, contrasting it with the mainstream approach. Using the examples of the Green New Deal, Medicare-for-All, and Build Back Better, it argues that rethinking spending and taxes as claims on, and releases of resources, respectively, leads to different conclusions about the affordability of these programs. Unlike the mainstream view, the MMT approach does not lead to the conclusion that taxes necessarily must go up to "pay for" more spending. Conversely, just because money is not a constraint does not mean that every government program is immediately "affordable". The resource demands of certain programs might be beyond the economy's potential, at least in the short-term. The MMT approach thus leads to different solutions for how to make a program "affordable"; to do so it focuses on creating the necessary resource space through the tools the government has at its disposal, such as public investment and taxation.
Keywords: 330